Role of Autophagy Markers (Light Chain 3B and Beclin-1) in Pathogenicity of Breast Cancer in a Sample of Iraqi Women: A Pilot Study - Aamal Awda Al-Mussawi, Hazma Mossa Alabassi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Breast cancer (BC) is the most common malignancy in women and the second greatest cause of cancer death. There are relatively little data available on the role of autophagy markers in pathogenicity of breast cancer in the Iraqi population. We have therefore investigated the role of Baclin-1 and LC3-B in pathogenicity of breast cancer in Iraqi women. Methods: A case-control study was conducted to assess the role of Bacline-1 and LC3-B in pathogenicity of breast cancer in Iraqi women. The study included 50 patients with BC age matched with 50 healthy individuals served as a control group. The Baclin-1 and LC3-B concentrations were determined by enzyme-linked immunosorbent assay (ELISA) technique. Results: Body mass index (BMI) were significantly increase in patients with BC compared to the controls. Serum Baclin-1 and LC3-B levels in cases were significantly higher (P= 0.001) than those in controls. According to histological tumor characteristics. Grade 2 and stage IIA were significantly higher in BC patients and the tumor grade and stage did not show any significant associations with serum levels of Bacline-1 and LC3-B. No significant correlation between serum levels of Baclin-1 and LC3-B (r = 0.034; P = 0.812). Conclusion: The study indicated that the Beclin-1 and LC3-B my consider a good biomarkers for progression of BC and it could be a therapeutic target to reduce the aggressiveness of disease.